2021
DOI: 10.1097/mnh.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and vascular calcification

Abstract: Purpose of reviewVascular calcification is a common and important cardiovascular risk factor in patients with chronic kidney disease (CKD). Recent advances in the understanding of the biology of vascular calcification implicate vitamin K-dependent proteins as important regulators in this process. This review highlights recent key advances in vascular biology, epidemiology, and clinical trials in this rapidly evolving field.Recent findingsVitamin K deficiency is associated with increasing severity of vascular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Conversely, vitamin K supplementation may boost antithrombotic activity, frequently diminished in those with vitamin K deficiency [ 55 ]. Since vitamin K exhibits procoagulant and anticoagulant properties, the balance between these effects can be influenced by the subtype-specific vitamin K administered [ 113 ]. Vitamin K1 may show a particularly pro-coagulative response, with the pro-coagulative proteins increasing more than proteins C and S [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, vitamin K supplementation may boost antithrombotic activity, frequently diminished in those with vitamin K deficiency [ 55 ]. Since vitamin K exhibits procoagulant and anticoagulant properties, the balance between these effects can be influenced by the subtype-specific vitamin K administered [ 113 ]. Vitamin K1 may show a particularly pro-coagulative response, with the pro-coagulative proteins increasing more than proteins C and S [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin K, as a health-promoting supplement, plays an important regulatory role in inflammation [ 20 ]. It has been shown that some vitamin K family members have the potential to reduce COVID-19 mortality and play an important role in SARS-CoV-2-induced lung injury and thromboembolism formation [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%